Proximate, functional, microbia, and sensory qualities of complementary food produced from acha (Digitaria exillis), malted pigeon pea (Cajanus cajan), grasshopper (Caelifera), and beetroot (Beta vulgaris L.) flour blends - Jummai Ibrahim; Jerome Adekunle Ayo; G.U Anikwueze; Tailem Paul (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2025)
Complementary feeding is the introduction of other foods (solid and liquids) when breast milk alone is no longer sufficient to support the nutritional requirements for the infant. This study evaluated the quality of complementary foods produced from acha, malted pigeon pea, grasshopper, and beetroot flours blends at varied ratios (100:0:0:0; 85:5:5:5;75:15:5:5; 80.10:5:5;75::15:5:5 and 70:5:20:5 respectively); focusing on functional, microbial, and sensory properties for infants with  age range from 6 to 24 months. The data obtained were analysed statistically using Statistical Package for Social sciences (25.0) and the average mean scores separated using Duncan’s Multiple Range Test (DMRT) at p<0.05. Results shows that the incorporation of these ingredients significantly enhanced functional characteristics such as bulk density, water absorption, swelling capacity and foaming capacity with a reduced bulk density from 0.68 to 0.41%, while foaming capacity increased from 21.00 to 59.00% respectively, water absorption capacity and swelling capacity ranged 57.67 to 90.40, 55.60 to 80.63 g/cm³ respectively, with added malted pigeon pea making the blends more suitable for infant feeding. Total heterotrophic fungal count total and heterotrophic bacteria count in samples (C1 to F3) decreased from 2.3×102 to 1.9×102and 2.7×105 to 2.1×105cfu respectively, in samples fortified with increased malted pigeon pea. While (F4 to F6) range from 3.1×102 to 4.3×102,   3.8×102 to 5.7×1023.2×102 to 4.2×102cfu with addition in grasshopper this, increase has been associated with moisture. The total coliform count, total heterotrophic bacteria count and total heterotrophic fungal count of the produced complementary food were however, better than ogi ranged from 1.6×102 – 2.8×102, 2.7×105 - 3.8×105 and1.5×105 - 3.1×103 cfu respectively while, cerelac recorded none. The possible bacteriaare Staphylococcus aureus, Bacillus cereus, Pseudomonas aeruginosa, Aspergillus niger, A. flavus, A. parasiticus, E. coli, Yeast. Sensory qualities showed acceptability in F3 and F6 respectively. These findings suggest that the blends, particularly F3 and F6 (Acha75%+Malted Pigeon pea15%+Grasshopper5%+Betroot5% and Acha70%+Malted Pigeon pea5%+Grasshopper20%+Betroot5%) are nutritionally adequate, safe, and highly acceptable complementary foods with strong potential to address protein-energy malnutrition and micronutrient deficiencies in infants. The study recommends further optimization, vitamin fortification, and strict hygienic processing to enhance the quality and scalability of these complementary foods.